Efektivitas Mediasi dalam Pencegahan Perceraian di Pengadilan Agama Kota Malang - Laila Dwi N., Nafidatul Rohmah; Novi Cindy L., Nur laila S.; Krisna Suci R., Wati Indah W; Yuznia A., Diza Alfi; Khasan Anwar, M. Ariyudanto D.H. (Ma’mal: Jurnal Laboratorium Syariah dan Hukum, 2020)
Abstract: This study discusses the problem of the effectiveness of mediation in the Religious Court of Malang City with the formulation of the problem: How is the effectiveness of mediation in preventing divorce in the Religious Court of Malang City? and what are the factors that become the supporters and obstacles to the success of the mediation in the Religious Court of Malang City ?. This writing uses a legal research method, namely sociological juridical. The result of this research is that the mediation which is carried out in the Religious Court of Malang City follows the reference of PERMA No. 01 of 2008 and has not been implemented effectively. The success of mediation is still low, many factors cause it, including the low level of community compliance in undergoing the mediation process, the culture of the community that thinks that divorce is not a disgrace for individuals or families and judges appointed as mediators still lack mastery of mediation theory. Keywords: Effectiveness of Mediation, Divorce, Peace.   Abstrak: Penelitian ini membahas permasalahan efektivitas mediasi di Pengadilan Agama Kota Malang dengan rumusan masalah: Bagaimana efektivitas mediasi dalam pencegahan perceraian di Pengadilan Agama Kota Malang? dan Faktor-faktor apa saja yang menjadi pendukung dan penghambat keberhasilan mediasi di Pengadilan Agama Kota Malang?. Penulisan ini menggunakan metode penelitian hukum yaitu yuridis sosiologis. Hasil dari penelitian ini adalah mediasi yang dilaksanakan di Pengadilan Agama Kota Malang mengikuti acuan dari PERMA No 01 Tahun 2008 dan belum berjalan secara efektif. Keberhasilan mediasi masih rendah, banyak faktor yang menjadi penyebabnya diantaranya adalah tingkat kepatuhan masyarakat dalam menjalani proses mediasi masih rendah, budaya masyarakat yang beranggapan bahwa perceraian bukanlah sebuah aib bagi pribadi maupun keluarga dan hakim yang ditunjuk sebagai mediator masih kurang menguasai teori mediasi. Kata kunci: Efektivitas  Mediasi,  Perceraian,  Perdamaian.